Calibration and control of in-plane Mg doping distribution in MgxZn1−xO/ZnO heterostructures grown by molecular beam epitaxy. (26th January 2015) - Uchida, Masaki; Falson, Joseph; Segawa, Yusaburo; Kozuka, Yusuke; Tsukazaki, Atsushi; Kawasaki, Masashi
Abstract: The in-plane Mg doping distribution in molecular beam epitaxy grown Mg x Zn1− x O/ZnO heterostructures is mapped by low-temperature photoluminescence measurements in an effort to evaluate and control the resultant inhomogeneity formed during the growth process. In an unrotated sample, the independent configuration effects of the O3 and Mg source cells are clearly demonstrated in a composition spread due to flux gradients, while this inhomogeneity is suppressed by sample rotation during the growth. The present mapping results provide an important means for investigating improved doping regimes with the aim of enhancing the quality of quantum transport observable at the Mg x Zn1− x O/ZnO heterointerface.